Matemática e deficiência visual - Brandão, Jorge Carvalho (2010)
The present study it deals with the learning of the concepts of triangles, quadrilaterals and symmetry for congenital, enclosed blind pupils in regular schools. It is mentioned, therefore, the formation of geometric concepts for blind citizens, different process of that one lived deeply by don’t blind pupils, since the first ones do not see the images that represent the geometric figures, a time that Plain Geometry presented in classrooms of regular schools to want the visualization of plain figures as a way of understanding of contents. She is necessary to think alternative ways for education for blind people, in function of the possibilities that these present. A possible way mentions the GEUmetria method to it, which considers the use of techniques of Orientation and Mobility in the geometry education. As motivation of this method it was used after confection of mockups lessons of Orientation and Mobility. Vygotsky was used as referential theoretician in the search for the understanding of the formation of concepts. As category of analysis the method was used Van Hiele of geometry education. Five citizens in Fortaleza - CE had been studied, during the year of 2008, pupils of regular schools, being three of Basic Teach and two of Average Teach. The previous knowledge of the learning before the introduction of the GEUmetria had been analyzed and each learning had its comparative performance obtains. It was observed that the GEUmetria method functioned in efficient way in four citizens, what allowed of this method to be applied by other professors of MAC or reinforcement of mathematics of pupils with visual deficiency. As future proposals, to analyze the understanding of concepts in Trigonometry